Energy expenditure and intensity of HIIT bodywork® session - Alexandre Fernandes Machado; Victor Machado Reis; Roberta Luksevicius Rica; Julien S. Baker; Aylton Jose Figueira Junior; Danilo Sales Bocalini (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: Several programs using total body weight exercise methods have been applied in several populations especially using HIIT. The present study assessed the oxygen consumption, heart rate, and energy expenditure of a HIIT body work® session. Methods: Twelve male participants performed 20 minutes of a HIIT body work, consisting of 20 sets of 30 seconds of stimulation in all-out intensity, followed by 30 seconds of passive recovery. Five cycles were performed for each exercise (jumping jack, burpee, mountain climb, and squat jump). Results: The mean VO2 of the session was 34 ± 7 ml.kg.min-1 (80.35% of the VO2 peak obtained in the session). The energy expenditure of the session was 251±27 kcal (13±1 kcal.min-1) and 39 ± 8 kcal (75±1 kcal.min-1) during the recovery time. The heart rate values were 160±18 bpm (91% of the peak HR of the session) and 125±22 bpm (71%) in recovery. In addition, significant differences (p<0.05) in maximal VO2 were found between jumping jack, mountain climber, burpee and squat jump. Conclusion: Based on the present data, a HIIT bodywork® session presented energy expenditure as a typical high-intensity exercise profile.